The feminized hero in Second Temple Judaism - Wills, Lawrence M. 1954- (Cambridge University Press, 2024)
The turbulent Second Temple period produced searching biblical texts whose protagonists, unlike heroes like Noah, Abraham, and Moses, were more everyday figures who expressed their moral uncertainties more vocally. Reflecting on a new type of Jewish moral agent, these tales depict men who are feminized, and women who are masculinized. In this volume, Lawrence M. Wills offers a deep interrogation of these stories, uncovering the psychological aspects of Jewish identity, moral life, and decisions that they explore. Often written as novellas, the stories investigate emotions, psychological interiorizing, the self, agency, and character. Recent insights from gender and postcolonial theory inform Wills' study, as he shows how one can study and compare modern and ancient gender constructs. Wills also reconstructs the social fabric of the Second Temple period and demonstrates how a focus on emotions, the self, and moral psychology, often associated with both ancient Greek and modern literature, are present in biblical texts, albeit in a subtle, unassuming manner
Keywords: Bible / Old Testament / Criticism, interpretation, etc; Heroes in the Bible; Bible stories, Hebrew / Social aspects; Sex role / Religious aspects / Judaism; Jews / Identity; Héros dans la Bible; Rôle selon le sexe / Aspect religieux / Judaïsme; Juifs / Identité